Heads of Schools Preparation of School Environment for Actualizing Student Mothers’ Continuation with Education in Public Secondary Schools in Dodoma Municipality (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aimed to investigate the heads of schools’ preparation of the school environment in actualizing student mothers’ continuation with education in public secondary schools in Dodoma municipality. Guided by the Clinical Supervision Model (CSM) developed by Goldhammar in 1969, the study used the convergent design under a mixed methods research approach. Targeted 40 heads of schools, 312 secondary school teachers, and 291 student-mothers, a sample of 6 heads of schools, 60 teachers, and 12 student-mothers was drawn, making a total of 78 respondents. Data was collected using questionnaires and interview guides whose validity was ensured by education experts in educational administration and planning. Based on the pilot test data, the reliability of teachers’ and student mothers’ questionnaires was established through Likert-type items where 0.81 and 0.75 Cronbach-Alpha coefficients were separately obtained with the aid of SPSS version 22. The credibility and dependability of the qualitative data gathered through interview guides were carried out through instrument triangulation and peer debriefing approaches. At the same time as the qualitative data were analyzed thematically and presented in quotations, the quantitative data were analyzed descriptively and tabulated in frequencies, percentages, and means. The study revealed that public secondary schools in Dodoma Municipality did not have on-site childcare facilities. The study also exposes that schools are striving for inclusive learning, but lack counseling, mentorship, financial aid collaboration, teacher professional development, and flexible academic programs. The study concluded that there are still inadequacies in assistance, even if school administrators have made strides toward fostering inclusive learning environments and honoring the accomplishments of student mothers. As adaptive academic programs are being introduced, additional supportive measures should be strengthened. Student mothers should participate in school-run initiatives and programs intended to assist them.